Multiple driving factors contribute to the variations of typical antibiotic resistance genes in different parts of soil-lettuce system - Xin Wen; Jiaojiao Xu; Guangfeng Xiang; Zhen Cao; Qiufan Yan; Jiandui Mi; Baohua Ma; Yongde Zou; Na Zhang; Xindi Liao; Yan Wang; Yinbao Wu (Ecotoxicology and Environmental Safety, 2021)
The application of manure compost may cause the transmission of antibiotic resistance genes (ARGs) in agroecological environment, which poses a global threat to public health. However, the driving factors for the transmission of ARGs from animal manure to agroecological systems remains poorly understood. Here, we explored the spatiotemporal variation in ARG abundance and bacterial community composition as well as relative driving factors in a soil-lettuce system amended with swine manure compost. The results showed that ARGs abundance had different variation trends in soil, lettuce phylloplane and endophyere after the application of swine manure compost. The temporal variations of total ARGs abundance had no significant different in soil and lettuce phylloplane, while lettuce endosphere enriched half of ARGs to the highest level at harvest. There was a significant linear correlation between ARGs and integrase genes (IGs). In contrast to the ARGs variation trend, the alpha diversity of soil and phylloplane bacteria showed increasing trends over planting time, and endosphere bacteria remained stable. Correlation analysis showed no identical ARG-related genera in the three parts, but the shared Proteobacteria, Pseudomonas, Halomonas and Chelativorans, from manure compost dominated ARG profile in the soil-lettuce system. Moreover, redundancy analysis and structural equation modelling showed the variations of ARGs may have resulted from the combination of multiple driving factors in soil-lettuce system. ARGs in soil were more affected by the IGs, antibiotic and heavy metals, and bacterial community structure and IGs were the major influencing factors of ARG profiles in the lettuce. The study provided insight into the multiple driving factors contribute to the variations of typical ARGs in different parts of soil-lettuce system, which was conducive to the risk assessment of ARGs in agroecosystem and the development of effective prevention and control measures for ARGs spread in the environment.